IMPACT OF ESTABLISHING A FARMER COOPERATIVE TO REACH THE WELFARE OF FARMERS IN INDONESIA - Ikhsan, M; Rukmana, D; Fahmid, IM; Tenriawaru, AN (Proceedings of the International Conference on Agriculture, 2023)
Farmer cooperative, a priority program that must be realized to improve the welfare of farmers who are the main support for economic growth in facing challenges, during COVID-19 pandemic. The problem in Indonesia is that most farmers only have a narrow farming scale or less than 0.5 ha, it is almost impossible for farmers to organize themselves effectively and efficiently. For this reason, the research aims to analyze the extent to which the interests of farmers’ corporations in improving the welfare of farmers. The research method is sourced from relevant stakeholders from the farmer level to the government, using a SWOT analysis and supporting secondary data, which was carried out in Demak Regency, Central Java Province. The results show that the rice farmer corporations in Demak Regency started from the Citra Kinaraya Multipurpose Cooperative (KSU) as a Primary Cooperative with its main business being the cultivation and marketing of specially packaged rice. Some of the products that have been produced include brown rice, black rice, milky rice and genki rice (mix) with a rice production capacity of around 40-50 tons/month. This capacity has only reached about 5% of the production target of around 875-1000 tons of special rice per month, which is produced from a harvested area of 18-20 ha·day. Currently the Citra Kinaraya Multipurpose Cooperative is developing into a Provincial Primary Cooperative by consolidating farmers outside the District of Demak, like District of Kudus, Grobogan, Banyumas, Sragen, Semarang and Purworejo. In 2020, it has been initiated that this corporation will become a Farmer Corporations Major Project implemented by the Ministry of Agriculture involving Ministries/Agencies and Local Governments and serve as a benchmark in developing 345 Farmer Corporations until 2024.